Oral health-related quality of life in chronic kidney disease patients - Adel Tabesh; Maryam Sadat Abtahi; Reyhane Narimany; Mansoureh Sadat Abtahi (Wolters Kluwer Medknow Publications, 2022)
Background: Chronic kidney disease (CKD) is a systemic disease with a major burden on several life aspects, including oral health. As life expectancy has improved in CKD patients, oral health status has become important regarding their quality of life. The aim of this study was to investigate oral health and oral health-related quality of life (OHRQoL) in CKD patients. Materials and Methods: This was a cross-sectional study. Patients' age, gender, and estimated glomerular filtration rate (eGFR) stage were recorded. Oral Health Impact Profile-14 (OHIP-14) was used to evaluate OHRQoL. Decayed, missing, and filled teeth (DMFT) index was utilized to record oral health status. SPSS software was used to analyze data. One-way ANOVA, t-test and Pearson/Spearman correlations were used. P < 0.05 was considered statistically significant. Results: One hundred and four patients participated; 60.6% male versus 39.4% female. Mean age was 52.1 ± 18.1 years. The most frequent eGFR stage was 5 (41.2%). Mean DMFT score was 18.7 ± 8.5. Mean OHIP-14 score was 14.82 ± 5.86. DMFT score was significantly correlated with OHIP-14 total score as well as its physical domains (P < 0.05). The correlation between eGFR stage and OHIP-14/DMFT score was both statistically significant (P = 0.03/P = 0.02, respectively). Conclusion: DMFT score was significantly correlated with OHRQoL in CKD patients, especially regarding its physical domains. Paying attention to fulfill dental treatment needs seems mandatory to improve OHRQoL and overall quality of life in these patients.